Elicit-Predict-Confront-Observe-Explain-Reinforce (EPCOER) Learning on Thermochemistry to Reduce Alternative Concept among Students with Different Initial Knowledge - Berlian Enggarani; Suhadi Ibnu; Aman Santoso (Universitas Negeri Malang, 2019)
Abstract: This study aimed to reduce the alternative concepts of students with EPCOER learning models and POE learning models on thermochemical material. This study used a test instrument in the form of three tier tests having 98% content validity. Cronbach Alpha reliability coefficient of 0.881 with a very high category. The research was conducted in two research classes at high school. The results showed a decrease in the alternative concepts that students had before learning. There were differences in the alternative concepts of students in the experimental and control classes, which students in experimental class had fewer alternative concepts compared to the student in the control class. The reduction in the alternative concepts of students were showed by the difference of students pretest and posttest scores. Key Words: EPCOER, initial knowledge, alternative concepts Abstrak: Penelitian ini bertujuan untuk mereduksi konsep alternatif siswa dengan model pembelajaran EPCOER dan model pembelajaran POE pada materi termokimia. Penelitian ini menggunakan instrumen tes berupa three tier test yang memiliki validitas isi 98% dengan kriteria sangat baik dan koefisien reliabilitas Alpha Cronbach 0,881 dengan kategori sangat tinggi. Penelitian ini dilakukan pada dua kelas di SMA. Hasil penelitian menunjukkan adanya penurunan konsep alternatif yang dimiliki siswa antara sebelum dan sesudah pembelajaran, di mana hasil penelitian konsep alternatif siswa pada kelas eksperimen dan kelas kontrol menunjukkan ada perbedaan. Hasil reduksi konsep alternatif siswa ditunjuk-kan oleh beda skor pretes dan postes siswa, di mana skor postes siswa lebih tinggi dari pada postes. Kata kunci: EPCOER, pengetahuan awal, konsep alternatif